A spontaneously immortalized muscle stem cell line (EfMS) from brown-marbled grouper for cell-cultured fish meat production - Ting Xue; Hongwei Zheng; Yaqi Zhao; Zhenxin Zhao; Jinwu Wang; Yue Zhang; Yaru Li; Song Wang; Yongliang Liu; Changhu Xue; Huarong Guo (Communications Biology)
Abstract Lacking of suitable fish muscle stem cell line has greatly hindered the fabrication of cell-cultured fish meat. Here, we established and characterized a spontaneously immortalized marine fish muscle stem cell line (EfMS) from brown-marbled grouper (Epinephelus fuscoguttatus), which could actively proliferate with good genetic stability and well maintain the stemness of myogenesis potential for over 50 passages. Taurine was found to be able to serve as a substitute of fish muscle extract in maintaining stemness. The EfMS cells could be efficiently induced to myogenic differentiation or adipogenic trans-differentiation in both 2D and 3D culture systems. Using edible 3D microcarriers, we produced 0.65 g fat-free and 1.47 g fat-containing cell-cultured fish meat in 8 days. The scaffold-free cell-cultured fish meat exhibited a much higher content of flavory amino acids than natural fish. Together, EfMS cell line can serve as an ideal seed cell line for the production of cell-cultured fish meat.